(untitled) (2002)
The fruit flies (Diptera:Tephritidae) constitute one of the main factors that restricts the fruits production, commercialization and export at international and national levels (Arévalo & Escobar, 2004).The fruit fly populations are commonly high in Colombia (Canal, 2004). The damage and the opportunity that these flies settle definitely in the country at a local level is worrying , this situation could lead to a fitosanitary problem of high relevance (Portillar, 1994). Therefore, the bioecology appropriate knowledge of the fly specie could set up handling conditions from their own habitat. Thus, the agents that can be used according to our environmental conditions and technological development could be identified, making a careful study of this knowledge about the tephritids natural enemies (parasitoids, predators and entomopathogens), including their recognition and bioecology as a choice of an initial population decrease of the fruit fly at national and local levels (Canal, 2004). Both parasitoids and predators were the main objective of this research, as a contribution for populations handling and control of the fruit fly in the influence area of Vélez, Santander-Colombia